Reintegrating the social sciences: The Dahlem Group - David Colander; Roland Kupers; Thomas Lux; Casey Rothschild (Middlebury College, Department of Economics, 2010)
Social science disciplines see themselves as distinct, with their own territory, their own methods, and their own framework. Within such an environment multidisciplinary work involves enormous conflict and translation problems. This situation is no longer acceptable. Dealing with modern problems requires researchers with broad transdisciplinary knowledge and with the ability to communicate with other social science researchers in a way that will allow them to arrive at transdisciplinary recommendations. Complex issues such as healthcare, income distributions, crime prevention, industrial policy, agriculture require not only insights from multiple social disciplines, but the integration of those insights. This document offers a proposal for training social science researchers. Specifically, it proposes reintegrating the social sciences by modifying the current system of training - which provides completely separate training for researchers in each sub-discipline - to incorporate a common first year 'core' of training for all social science researchers. If implemented, the proposal will reduce the babble that currently characterizes much of the interdisciplinary conversations.
Keywords: 330